AI and the Humanities in a Future-Ready Education Phase - Subhan, Mohd Aidil (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Today, our children are born digital natives. But we must still give them more deliberate exposure to AI. This will help them better understand the nuances, limitations and abilities of AI tools. Not everyone may have the inclination to go far in this field. But everyone should have the opportunity to develop a basic understanding and proficiency. With this foundation, they will be able to better harness AI’s innovative potential, and make it a valuable tool in whatever field they choose to pursue later in life.